Multiple Autoimmune Syndrome (Graves’ Disease, Autoimmune Hepatitis, SLE) in Young Male with ASD Secundum: A Rare Case - Dinar Dewi Miftah Tyas Arum; Herlina Kusuma Dewi; Eva Niamuzisilawati; Aritantri Darmayani; Agus Joko Susanto; Astri Kurniati Martiana; Brian Wasita (‎ InaJEMD - Indonesian Journal of Endocrinology Metabolic and Diabetes, 2025)
Multiple autoimmune syndrome (MAS) is characterized by the presence of at least three autoimmune diseases, presenting complex clinical challenges due to overlapping conditions and varied manifestations. Multiple autoimmune syndrome is rarely reported in men, particularly with the combination of Graves’ disease, systemic lupus erythematosus (SLE), and autoimmune hepatitis (AIH). We report a case of a 22-year-old male who presented with symptoms of jaundice, significant weight loss, and classic signs of hyperthyroidism, including palpitations and tremors. Physical examination revealed jaundice, exophthalmos, and an enlarged thyroid gland, and he was diagnosed with Graves' disease, SLE, and AIH. Additional findings included stasis dermatitis and an atrial septal defect (ASD) with a moderate risk of pulmonary hypertension. The patient received thiamazole, propranolol, and corticosteroids, leading to clinical stabilization and symptom resolution. This rare MAS case with concurrent Graves’ disease, SLE, and AIH highlights the need for accurate diagnosis and individualized management. The immunological interplay among these diseases contributes to diverse clinical manifestations, requiring a multidisciplinary approach. Our patient’s management strategy effectively controlled hyperthyroidism, mitigated hepatic inflammation, and stabilized cardiac function, illustrating the effectiveness of comprehensive therapy. In young patients presenting with multiple autoimmune symptoms, MAS should be considered, especially with unusual combinations. Early detection and tailored treatment approaches, along with interdisciplinary collaboration, are essential to manage MAS and its associated complications.